2004
DOI: 10.1038/modpathol.3800032
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MUC1 (EMA) and E-cadherin in renal cell carcinoma: a systematic immunohistochemical analysis of 188 cases

Abstract: MUC1 (epithelial membrane antigen) is a membrane-associated mucin known to interfere with both cell-cell and cell-matrix adhesions. Overexpression has been associated with poor prognosis in a variety of cancers. We investigated the expression of MUC1 (using two different antibodies, MA695 and E29) and E-cadherin in renal cell carcinomas (137 conventional, 23 chromophobe, 20 papillary, and eight unclassified tumors) with respect to diagnostic and prognostic significance using a tissue microarray technique. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 43 publications
5
44
1
1
Order By: Relevance
“…Chromophobe RCC has been reported to express E-cadherin, while papillary RCC has been shown to be a non-expresser of E-cadherin. 32 As expected, chromophobe RCC cells exhibited membranous E-cadherin immunoreactivity, but no nuclear protein was found. Papillary RCC was negative for E-cadherin immunoreactivity (Figure 1c).…”
Section: Nuclear Localization Of E-cadherin Is Associated With Cc-rccmentioning
confidence: 75%
See 1 more Smart Citation
“…Chromophobe RCC has been reported to express E-cadherin, while papillary RCC has been shown to be a non-expresser of E-cadherin. 32 As expected, chromophobe RCC cells exhibited membranous E-cadherin immunoreactivity, but no nuclear protein was found. Papillary RCC was negative for E-cadherin immunoreactivity (Figure 1c).…”
Section: Nuclear Localization Of E-cadherin Is Associated With Cc-rccmentioning
confidence: 75%
“…Notably, chromophobe RCC is known to express E-cadherin, while papillary RCC has been shown to be a non-expresser of E-cadherin. 32 Nuclear E-cadherin and VHL in CC-RCC ML Gervais et al in the representative Figure 1b (and data not shown) representing a CC-RCC sample from patient no. 9 shown to have F136S substitution mutation in VHL (Table 1).…”
Section: Nuclear Localization Of E-cadherin Is Associated With Cc-rccmentioning
confidence: 99%
“…This observation is consistent with a recent study showing that most papillary RCC, which displayed Ecadherin, were of type 2. 8 These observations suggested that a significant portion of RCC display a dual differentiation, which may or may not be appreciated at light microscopic level. The explanation for dual differentiation within a single tumor is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Some histochemical stains and immunohistochemical markers are shown to be helpful in the differential diagnosis of these tumors. Hale's colloidal iron stain can support the diagnosis for chromophobe RCC, 1,2 and immune markers such as vimentin, 3,4 CD10, 5 parvalbumin, 6,7 E-cadherin, 8 or RCC marker 5,9 have been used to aid in the diagnosis and classification of renal neoplasms. These special studies are, however, quite limited.…”
mentioning
confidence: 99%
“…Linker sequences carrying a 5V NotI restriction site and coding for either (G 4 S) 4 or (G 4 S) 2 C(G 4 S) 2 were introduced in front of the VH domain of a scFv, cloned in pCANTAB 5E, by consecutive insertional mutagenesis using the QuickChange mutagenesis kit (Stratagene, La Jolla, CA); the resulting clones were named LscFv. Final di-scFv-C constructs were assembled by ligation of the NotI insert of the LscFv clones into the unique NotI restriction site present at the 3V end of the corresponding scFv cloned in pCANTAB 5E or pCANTAB 5E-Cys.…”
Section: Pretargeted Radioimmunotherapy Developmentmentioning
confidence: 99%